2021
DOI: 10.1002/ece3.7493
|View full text |Cite
|
Sign up to set email alerts
|

Multisource noninvasive genetics of brown bears (Ursus arctos) in Greece reveals a highly structured population and a new matrilineal contact zone in southern Europe

Abstract: In human‐dominated landscapes, connectivity is crucial for maintaining demographically stable mammalian populations. Here, we provide a comprehensive noninvasive genetic study for the brown bear population in the Hellenic Peninsula. We analyze its population structuring and connectivity, estimate its population size throughout its distribution, and describe its phylogeography in detail for the first time. Our results, based on 150 multilocus genotypes and on 244‐bp sequences of the mtDNA control region, show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 99 publications
(106 reference statements)
2
9
0
Order By: Relevance
“…Regarding the 65 unique bears found in Pindos, our findings show that they are characterized by relatively high genetic diversity and low values for Fis in the majority of loci. This declares a low inbreeding level of the population, which agrees with some of the previous studies [ 9 , 26 ] that are shown in Table 10 . Therefore, high genetic diversity combined with low inbreeding coefficient and relatively high Nc/Ne ratio, shows that the bear population in Pindos NP is not currently threatened by genetic instability [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Regarding the 65 unique bears found in Pindos, our findings show that they are characterized by relatively high genetic diversity and low values for Fis in the majority of loci. This declares a low inbreeding level of the population, which agrees with some of the previous studies [ 9 , 26 ] that are shown in Table 10 . Therefore, high genetic diversity combined with low inbreeding coefficient and relatively high Nc/Ne ratio, shows that the bear population in Pindos NP is not currently threatened by genetic instability [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…To our knowledge, this is the first study that includes bears from the overall area of Prespa National Park (MBPNP), but there are studies that have conducted genetic analysis of bears from regions close or part of MBPNP (e.g., Peristeri, Kastoria, Amyntaio) [ 6 , 9 , 59 ]. Based on the genetic data produced from this study we found that in the Prespa population the microsatellite loci are informative for the estimation of the population size and we can use them for the analysis of genetic variance (PIC > 0.5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the genetic studies conducted on brown bear populations from Europe estimated the number of individuals, their density, and sex ratio to reveal the species' conservation status and distribution [69,81]. Some authors made assumptions and demonstrated the current need for connectivity between bear populations starting from these indicators [56,64,65,71,76,79,80,84,87,89,107] or the sex-biased philopatry [53,65,74,79,95,[156][157][158].…”
Section: Noninvasive Genetics In Bear Conservation and Managementmentioning
confidence: 99%